Adverse life events, area socio-economic disadvantage, and adolescent psychopathology: the role of closeness to grandparents in moderating the effect of contextual stress - Flouri, Eirini; Buchanan, Ann; Tan, Jo Pei; Griggs, Julia; Attar-Schwartz, Shalhevet (Informa Healthcare, 2010)
The study, using data from 801 11–16-year-olds clustered in 68 schools across England and Wales, tested whether closeness to grandparents moderates the association between contextual stress and adolescent psychopathology and prosocial behavior, measured with the strengths and difficulties questionnaire (SDQ). Contextual stress was measured at both school area level (assessed with the index of multiple deprivation) and child level (assessed, as life stress, with the number of proximal and distal adverse life events experienced). At baseline, area stress (multiple deprivation) was unrelated to psychopathology (SDQ), and although both proximal (during the last 12 months) and distal (before the last 12 months) life stress was associated with broad and specific child psychopathology, the association with proximal life stress was stronger. Closeness to the most significant grandparent moderated both the effect of proximal life stress on hyperactivity and broad psychopathology, and the effect of the interaction between distal and proximal life stress on broad and externalizing psychopathology. These findings suggest that the role of grandparents deserves further attention in future investigations of the development of resilience in youth.